Improving Family-School Collaboration in Transition Services for Students with Intellectual Disabilities: A Framework for School Psychologists. Issue 3 (3rd July 2019) - Talapatra, Devadrita; Miller, Gloria E.; Schumacher-Martinez, Ruth
ABSTRACT: Strong collaborative partnerships between families, schools, and communities are essential to promote successful postgraduation outcomes for students with intellectual disabilities (ID) and are a key feature of a new Transition Planning, Implementation, and Evaluation (TPIE) framework. The purpose of this article is to provide an overview of the proactive roles school psychologists can play in guiding this three-phase framework while ensuring family engagement in the critical transition process and activities embedded in this framework. School psychologists are ideally suited to foster collaborative partnerships that can lead to comprehensive transition programming and services to promote the long-term life success of youth with ID.